2022
DOI: 10.1002/asjc.2713
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time data‐driven PID controller for multivariable process employing deep neural network

Abstract: The complex industrial processes exhibiting nonstationary and multivariable with time‐varying dynamics result in low accuracy. Also, stability compensation is difficult to be obtained by a conventional PID controller. Hence, a deep learning‐based data‐driven PID controller is designed for unmodeled dynamics compensation for complex industrial processes. In this research work, a nonlinear PID controller is designed with a deep neural network (DNN) model from unmodeled dynamics of the complex industrial processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The proposed control algorithm has the advantage of not needing any system parameters and dynamics for target value tracking. Related previous works are based on model-free adaptive control [3], [4], [5], [6], [7], [8], [9], [10], [11], data-driven control, and artificial intelligence control [16], [17], [18], [19], [20], [21]. In the previous related works, generally, the conventional proportional-integral-derivative control scheme was adopted, and the gain adaptation law was proposed using various methods.…”
Section: Concept Of Data-driven Adaptive Steady-state-integral-deriva...mentioning
confidence: 99%
See 3 more Smart Citations
“…The proposed control algorithm has the advantage of not needing any system parameters and dynamics for target value tracking. Related previous works are based on model-free adaptive control [3], [4], [5], [6], [7], [8], [9], [10], [11], data-driven control, and artificial intelligence control [16], [17], [18], [19], [20], [21]. In the previous related works, generally, the conventional proportional-integral-derivative control scheme was adopted, and the gain adaptation law was proposed using various methods.…”
Section: Concept Of Data-driven Adaptive Steady-state-integral-deriva...mentioning
confidence: 99%
“…Because the derivative of function of the Lyapunov candidate with respect to time t should always be negative for asymptotic stability, the derivative of the function J with respect to time t was derived and used for stability analysis. Using (16), the derivative of J with respect to time t can be derived as follows [10], [17].…”
Section: Stability Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers in Liu et al (2021b) suggested the improved distributed differential evolution (DDE)-based meta-heuristic method for training the NN-based control model applied to uncertain nonlinear plants. Jeyaraj and Nadar (2022) proposed an online adaptive PID control approach applied to nonlinear MIMO plants based on NN learning method. The principal disadvantage of these NN controllers relates to the enormous computing-time that hampers the facilitation of these schemes in practice.…”
Section: Introductionmentioning
confidence: 99%